Empirical relationship between board characteristics, earnings management, insolvency risk, and corporate social responsibility - Hosam Alden Riyadh; Maher A. Al-Shmam; Mohammed Ghanim Ahmed (Cogent Business & Management, 2024)
The study aims to investigate the relationship between board characteristics, earnings management, insolvency risk, and corporate social responsibility (CSR). The first objective examines the relationship between the board of directors' characteristics (i.e. board financial expertise, ownership concentration, and board size) and earnings management during the ISIS (Islamic State of Iraq and Syria) crisis, and the second discusses earnings management and insolvency risk of local banks. Third, this research aims to consider earnings management as a mediator between board characteristics and insolvency risk, while the fourth purpose is to consider CSR involvement as a moderator in the relationship between earnings management and insolvency risk. To achieve these objectives, a quantitative method and secondary data were used on 35 banks from 2010 to 2020. Data from Iraqi-listed firms' annual reports and Smart PLS were employed for analysis. The analysis results demonstrated that the relationship between board characteristics (board financial expertise, concentration of ownership, and board size) had negative impacts on earnings management and a significant negative impact on insolvency risk. Correspondingly, earnings management mediated between board characteristics (board financial expertise, the concentration of ownership, and board size) and insolvency risk. Furthermore, CSR was an impactful moderator in the relationship between earnings management and insolvency risk.This research has investigated the relationship between board characteristics, earnings management, insolvency risk, and corporate social responsibility (CSR). The first objective examines the relationship between the board of directors' characteristics (i.e. board financial expertise, ownership concentration, and board size) and earnings management during the ISIS (Islamic State of Iraq and Syria) crisis, and the second discusses earnings management and the insolvency risk of local banks. Third, this research aims to consider earnings management as a mediator between board characteristics and insolvency risk, while the fourth purpose is to consider CSR involvement as a moderator in the relationship between earnings management and insolvency risk. To achieve these objectives, a quantitative method and secondary data were used on 35 banks from 2010 to 2020. Data from Iraqi-listed firms' annual reports and Smart PLS were employed for analysis. The analysis results demonstrated that the relationship between board characteristics (board financial expertise, concentration of ownership, and board size) had negative impacts on earnings management and a significant negative impact on insolvency risk. Correspondingly, earnings management mediated between board characteristics (board financial expertise, the concentration of ownership, and board size) and insolvency risk. Furthermore, CSR was an impactful moderator in the relationship between earnings management and insolvency risk.
Keywords: G34; M14; M41; 650; Board characteristic; insolvency risk; earnings management; corporate social responsibility